Morphometric Study of Maximum Antero-Posterior and Curved Antero-Posterior Diameter of the Head of the Dry Humerus Bone (Community Based Medical Journal, 2025)
The humerus is a typical long bone of the upper limb; its head articulates with the glenoid cavity of the scapula to form the shoulder joint. The rounded head of the humerus is too weakly supported in the scapular glenoid cavity lined by the glenoid labrum; hence, it forms one of the most mobile and most unstable joints. Our study aims to determine the morphometry of the dry humeral head. This cross-sectional, descriptive study was carried out in the Department of Anatomy, Mymensingh Medical College, Bangladesh, from July 2021 to June 2022. We took 100 (right=43 and left=57) samples through the purposive sampling. Any damaged, unossified or fractured bones were excluded. The maximum anteroposterior diameter of the head of the humerus was measured by using digital slide calipers, while the curved anteroposterior diameter of the head was measured by using flexible measuring tape. The mean anteroposterior diameter of the head was found 38.665±3.206 mm at right side and 38.321±3.115 mm at left side. The mean curved anteroposterior diameter of the head was found 57.116±5.499 mm and 54.789±4.977 mm at right and left side respectively. Our findings are expected to be helpful for clinical anatomists, orthopedic surgeons, anthropologists, and radiologists for academic teaching and clinical decision making.CBMJ 2025 January: Vol. 14 No. 01 P: 66-69